2013
DOI: 10.1371/journal.pone.0055955
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Factors Associated with Postpartum Visits in Rural China

Abstract: BackgroundPostpartum visits (PPVs) have been advocated as a way to improve health outcomes for mothers and their infants, but the rate of PPVs is still low in rural China. This study aims to investigate the utilization of PPVs and to explore the factors associated with PPVs in rural China. Parity is the most concerned factor in this study.MethodsA cross-sectional household survey was performed in two counties of Zhejiang province. Questions include socio-economic, health services and women's delivery data. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…EPDS scores at T1 were higher than T3. However, studies in China tended to pay more attention to the period of 6–8 weeks postpartum among the primiparas [ 31 – 33 ]. We observed that the prevalence of depression was highest at the late pregnancy among our primiparas sample.…”
Section: Discussionmentioning
confidence: 99%
“…EPDS scores at T1 were higher than T3. However, studies in China tended to pay more attention to the period of 6–8 weeks postpartum among the primiparas [ 31 – 33 ]. We observed that the prevalence of depression was highest at the late pregnancy among our primiparas sample.…”
Section: Discussionmentioning
confidence: 99%
“…Stratified multistage cluster sampling was conducted to obtain the sample as follows: 5 towns were selected from each of the two counties, 2 villages were selected from each town, and then families were selected from each village. The final sample was from 2000 families in 20 villages of 10 towns in the 2 counties [ 9 ]. To analyze the changes, the same villages were selected in the past three surveys.…”
Section: Methodsmentioning
confidence: 99%
“…Trained investigators were asked to conduct face-to-face interview to collect the data with the questionnaire. The organization, direction, inspection, and quality control of the survey were conducted by the trained directors [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding to the studies performed in other countries, there is a large variation of rates of maternal postnatal visits. The followings rates have been mentioned: 35 %, for Congo [ 6 ], 68.6 %, for China [ 8 ], and 85 %, for Unites States of America [ 2 ]. Comparison of rates of attendance to maternal postnatal visits among countries is difficult because the timing (as well content) of maternal postnatal visits varies widely.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicates that health care coverage in the postpartum period is close to 90 % in developed countries [ 5 ], while rates are much lower in low- and middle-income countries. In general, the rate of attendance to postpartum visits is low varying from 34.6 %, in Congo [ 6 ] to 70 %, in Lebanon [ 7 ] and China [ 8 ]. Although studies have focused on the postpartum visit, usually limited at the first 3 or 4 months, a gynecological appointment at any time after childbirth (GA) is important for several reasons.…”
Section: Introductionmentioning
confidence: 99%